Synthesis and characterization of azo amidazole ligand type N2 and metal complexes with di valence cobalt , nickel and copper - Abdualameer Jawad, Shatha (Al-Qadisiyah Journal of Pure Science, 2018)
The bi dentate ligand type N2 have been prepared through two steps . The first included the reaction between one equivalent of benzil with one equnivalent of hexa methylene tetra amine, the second included the reaction of first step precursor with one equnivalent of diazanium chloride ( p- ethyle aniline with acidic sodium nitrate ) , to obtained the target ligand . Co+2 , Ni+2 , Cu+2 from there action of the ligand Complexes were prepared with metal ions 1:1 ratio , the prepousd compounds were characterized by FT-IR , UV-Vis , NMR for ligand , C.H.N Elemental analysis spectoscopies , as well as the molar conductivity and magneticthe successptibility . suggested geometry around the cobalte and copper ions is octahedral and Square planer around nickel ion.